Body mass index as a proxy indicator for poor oral hygiene habits in adult diabetic patients - Ranfl Martin; Vurzer Blaž; Zaletel-Kragelj Lijana (Sciendo, 2022)
To analyse if body mass index (BMI) could be used as a fast proxy indicator of poor oral hygiene habits (POHH) among the adult population with diabetes mellitus.